Electrocardiography in Chagas' heart disease - Sérgio A.C. Garzon; Adalberto M. Lorga; José Carlos Nicolau (São Paulo Medical Journal)
Conventional ECG still plays an important role in the overall knowledge of Chagas' cardiopathy, because of its importance in longitudinal and epidemiological studies, its diagnostic value, and its utility in prognostic evaluation. The authors discuss these aspects, as well as the use of ECG in the acute phase and the significance of a normal ECG in Chagas' disease. Correlations were made between ECG and hemodynamic/angiographic variables among 1010 patients with positive laboratory tests for Chagas' disease: a) in the group with normal ECG there were no significant differences between symptomatic and non-symptomatic patients with regard to ejection fraction and angiographic abnormalities; b) slight abnormalities on the ECG corresponded to an intermediate level of severity of the disease, that is, between normal ECG and ECG with significant abnormalities; c) fibrosis on the ECG was not predictive of akinesia in the related area on the angiography; d) combined ECG abnormalities generally correlated with greater myocardial compromise compared to isolated abnormalities; e) under multiple regression analysis the ECG abnormalities that independently correlated with depressed ejection fraction were: premature ventricular beats, ventricular tachycardia, left bundle branch block, atrial fibrillation, complete AV block, and anterior and inferior fibrosis. Male sex, cardiac insufficiency and cardiomegaly on the thorax radiography were also significantly related.